2016
DOI: 10.1002/iub.1473
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory cytokines prime adipose tissue mesenchymal stem cells to enhance malignancy of MCF‐7 breast cancer cells via transforming growth factor‐β1

Abstract: Mesenchymal stem cells from human adipose tissue (hASCs) are proposed as suitable tools for soft tissue engineering and reconstruction. Although it is known that hASCs have the ability to home to sites of inflammation and tumor niche, the role of inflammatory cytokines in the hASCs-affected tumor development is not understood. We found that interferon-c (IFN-c) and/or tumor necrosis factor-a (TNF-a) prime hASCs to produce soluble factors which enhance MCF-7 cell line malignancy in vitro. IFN-c and/or TNF-a-pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…Expression of TGF- β in adipose tissue MSCs can be stimulated by inflammatory cytokines presented in TME, such as IFN- γ and TNF- α . It has been reported that TGF- β produced by cytokine-primed adipose tissue MSCs contribute to EMT, migration, and invasiveness of breast cancer cells [103]. These findings indicate important role of TGF- β not only in regulation of tumor cells behavior, but also in determination of MSC activity in inflammatory TME.…”
Section: Tgf-βmentioning
confidence: 73%
“…Expression of TGF- β in adipose tissue MSCs can be stimulated by inflammatory cytokines presented in TME, such as IFN- γ and TNF- α . It has been reported that TGF- β produced by cytokine-primed adipose tissue MSCs contribute to EMT, migration, and invasiveness of breast cancer cells [103]. These findings indicate important role of TGF- β not only in regulation of tumor cells behavior, but also in determination of MSC activity in inflammatory TME.…”
Section: Tgf-βmentioning
confidence: 73%
“…MSCs are able to effectively inhibit the proliferation of T-cells, B-cells, NK, and dendritic cells because of their production and secretion of molecules such as TGF- β , PGE2, and indoleamine-pyrrole 2,3-dioxygenase (IDO) [171, 172]. Furthermore, Tumor Necrosis Factor Alfa (TNF- α ) activates MSCs to secrete chemokine (C-C motif) ligand 5 (CCL5), C-C chemokine receptor type 2 (CCR2), and the interleukin 8 receptor, beta ( CXCR2) ligands that in turn recruit CXCR2+ neutrophils into the tumor.…”
Section: Mscs and Cancer Cellsmentioning
confidence: 99%
“…TNFα is present in high concentrations throughout the breast tumor/ stroma milieu, and upon activation of TNFα receptors, can trigger a powerful perpetual cascade of NF-κB activation [23,24]. epithelial-to-mesenchymal transition [25] and sustained release of diverse chemokines (i.e., CCL2/CCL5) [26]. Chemokines in turn ultimately trigger inward migration of a large number of leukocyte sub-populations (LSPs) bearing CCR2 / CCR5 receptors that embed into the tumor, and further drive tumor aggression and stem cell survival.…”
Section: Introductionmentioning
confidence: 99%